Rapid estimation of lives of deficient superpave mixes and laboratory-based accelerated mix testing models - Manandhar, Chandra Bahadur (Kansas State University, 2010)
The engineers from the Kansas Department of Transportation (KDOT) often have to decide whether or not to accept non-conforming Superpave mixtures during construction. The first part of this study focused on estimating lives of deficient Superpave pavements incorporating nonconforming Superpave mixtures. These criteria were based on the Hamburg Wheel-Tracking Device (HWTD) test results and analysis. The second part of this study focused on developing accelerated mix testing models to considerably reduce test duration. To accomplish the first objective, nine fine-graded Superpave mixes of 12.5-mm nominal maximum aggregate size (NMAS) with asphalt grade PG 64-22 from six administrative districts of KDOT were selected. Specimens were prepared at three different target air void levels @ N[subscript]design gyrations and four target simulated in-place density levels with the Superpave gyratory compactor. Average number of wheel passes to 20-mm rut depth, creep slope, stripping slope, and stripping inflection point in HWTD tests were recorded and then used in the statistical analysis. Results showed that, in general, higher simulated in-place density up to a certain limit of 91% to 93%, results in a higher number of wheel passes until 20-mm rut depth in HWTD tests. A Superpave mixture with very low air voids @ N[subscript]design (2%) level performed very poorly in the HWTD test. HWTD tests were also performed on six 12.5-mm NMAS mixtures with air voids @ N[subscript]design of 4% for six projects, simulated in-place density of 93%, two temperature levels and five load levels with binder grades of PG 64-22, PG 64-28, and PG 70-22. Field cores of 150-mm in diameter from three projects in three KDOT districts with 12.5-mm NMAS and asphalt grade of PG 64-22 were also obtained and tested in HWTD for model evaluation. HWTD test results indicated as expected. Statistical analysis was performed and accelerated mix testing models were developed to determine the effect of increased temperature and load on the duration of the HWTD test. Good consistency between predicted and observed test results was obtained when higher temperature and standard load level were used. Test duration of the HWTD can thus be reduced to two hours or less using accelerated mix testing (statistical) models.
Keywords: Superpave mixes; Hamburg wheel-tracking device; Hot-mix asphalt; Accelerated mix testing models; Rapid estimation of asphalt pavement life; Moisture damage; Engineering, Civil (0543); Engineering, Materials Science (0794)